2004
DOI: 10.1126/science.1092780
|View full text |Cite
|
Sign up to set email alerts
|

G Protein-Coupled Receptor-Dependent Development of Human Frontal Cortex

Abstract: The mammalian cerebral cortex is characterized by complex patterns of anatomical and functional areas that differ markedly between species, but the molecular basis for this functional subdivision is largely unknown. Here, we show that mutations in GPR56 , which encodes an orphan G protein–coupled receptor (GPCR) with a large extracellular domain, cause a human brain cortical malformation called bilateral frontoparietal polymicrogyria (BFPP). BFPP is characterized by disorganized cortica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
417
2
4

Year Published

2006
2006
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 496 publications
(434 citation statements)
references
References 30 publications
11
417
2
4
Order By: Relevance
“…There is, however, an overlap with other conditions as mentioned previously. Patients with GPR56 mutations have bilateral frontoparietal polymicrogyria seen in an anteroposterior distribution, bilateral patchy white matter changes and brainstem and cerebellar hypoplasia (282). Whilst the MRI findings are clearly similar to those seen in the midgroup of patients reported here (12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23), the polymicrogyria seen in patients with GPR56 mutations affects predominantly the fronto-parietal regions and not the temporal and occipital areas also seen in patient with a dystroglycanopathy (302).…”
Section: Discussionsupporting
confidence: 49%
“…There is, however, an overlap with other conditions as mentioned previously. Patients with GPR56 mutations have bilateral frontoparietal polymicrogyria seen in an anteroposterior distribution, bilateral patchy white matter changes and brainstem and cerebellar hypoplasia (282). Whilst the MRI findings are clearly similar to those seen in the midgroup of patients reported here (12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23), the polymicrogyria seen in patients with GPR56 mutations affects predominantly the fronto-parietal regions and not the temporal and occipital areas also seen in patient with a dystroglycanopathy (302).…”
Section: Discussionsupporting
confidence: 49%
“…The same may also be true for human disease genes causing regional cortical malformations (Barkovich et al, 2012). For example, mutations in GPR56 were initially identified as causative of regional polymicrogyria, only in the frontoparietal cortex while sparing the rest of the brain (Piao et al, 2004). Recently it has been demonstrated that GPR56 expression is strictly regionalized and regulated in a very complex manner, and new subtle mutations in its enhancer regions have been recently identified as causative of patterned cortical malformations in humans.…”
Section: Beyond Cortical Expansion: Gyrificationmentioning
confidence: 99%
“…More recently, deficiency in GPS cleavage has been linked to human genetic disorders. As such, point mutations affecting the GPS cleavage of GPR56 and polycystin-1 have been implicated as the causes of bilateral frontoparietal polymicrogyria (BFPP) and autosomal dominant polycystic kidney disease (ADPKD), respectively [14,15]. Therefore, GPS cleavage appears to be an inherent and essential post-translational modification for the expression, presentation and function of adhesion-GPCRs.…”
Section: Introductionmentioning
confidence: 99%